Exploring the material and dielectric properties of poly(vinylidene fluoride) composites incorporated with graphene and graphene oxide - Guner, Melek; Cicek Ozkan, Betul; Ozdemir, Niyazi (Royal Soc Chemistry, 2024)
This study focuses on enhancing the structural, thermal, and dielectric properties of poly(vinylidene fluoride) (PVDF) nanocomposites loaded with graphene oxide (GO) and graphene (G), synthesized via solution casting. Characterization techniques, including X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA), revealed significant enhancements due to the nanofillers. The crystallinity of PG composites increased to 60.39% from 49.21% in neat PVDF, transitioning from alpha to beta phases, which is beneficial for high-performance electronics and energy storage. PG composites showed a dielectric constant (epsilon ') of 10.50, higher than those of neat PVDF (epsilon ' = 7.54) and PGO composites (epsilon ' = 8.56). The dielectric loss (tan delta) for PG was low at 0.15, suitable for electronics. The AC conductivity of PG composites (2.22 x 10-7 S cm-1) was higher than those of neat PVDF (1.09 x 10-7 S cm-1) and PGO (1.65 x 10-7 S cm-1), enhancing their suitability for flexible electronics. Thermal stability assessments showed that PG composites had the highest degradation temperature at 471.04 degrees C, indicating improved thermal resistance. These enhancements are due to the effective dispersion and interaction of graphene-based nanofillers within the PVDF matrix. This study demonstrates that incorporating nanofillers into polymer composites significantly advances materials science by enhancing the dielectric properties for various industrial applications. This study focuses on enhancing the structural, thermal, and dielectric properties of poly(vinylidene fluoride) (PVDF) nanocomposites loaded with graphene oxide (GO) and graphene (G), synthesized via solution casting.
Keywords: Nanocomposites; Pvdf/Graphene; Membranes; Polymorph; Matrix